2017
DOI: 10.1038/s41467-017-02183-y
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and characterization of two functional variants in the human longevity gene FOXO3

Abstract: FOXO3 is consistently annotated as a human longevity gene. However, functional variants and underlying mechanisms for the association remain unknown. Here, we perform resequencing of the FOXO3 locus and single-nucleotide variant (SNV) genotyping in three European populations. We find two FOXO3 SNVs, rs12206094 and rs4946935, to be most significantly associated with longevity and further characterize them functionally. We experimentally validate the in silico predicted allele-dependent binding of transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 69 publications
4
73
0
1
Order By: Relevance
“…, ; Flachsbart et al. ; Joshi et al. ), our results are consistent with the hypothesis that loci in these canonical pathways might be under selective constraints (see Remolina et al.…”
Section: Resultssupporting
confidence: 91%
“…, ; Flachsbart et al. ; Joshi et al. ), our results are consistent with the hypothesis that loci in these canonical pathways might be under selective constraints (see Remolina et al.…”
Section: Resultssupporting
confidence: 91%
“…Forkhead box O3 is a longevity factor that has been implicated in human lifespan extension (Flachsbart et al, ; Martins et al, ). Given that FoxO3 is evolutionally conserved, it is possible that FoxO3 prevents the aging process of organs and cells in different organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vitro and in vivo studies have demonstrated FoxO3 as a longevity factor that plays an important role in lifespan extension in different organisms, including humans (Flachsbart et al, ; Martins et al, ; Wessells, Fitzgerald, Cypser, Tatar, & Bodmer, ). These previous studies have strongly proposed that the longevity factor FoxO3 might be a suitable target for preventing the aging process of organs and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these results suggest that FOXO3 genetic variants contribute to reaching old age, but there is a paucity of human studies that are sufficiently powered to demonstrate the role of FOXO3 in healthy aging 60 . One mechanism of action of the FOXO3 SNPs was only recently uncovered and involves a complex “interactome” whereby cellular stress causes FOXO3 to move close and physically interacts with no fewer than 46 flanking genes on chromosome 6 64 .…”
Section: Foxo3 and The Genetics Of Longevitymentioning
confidence: 95%